Investigations of chromium (VI) ion sorption and reduction on strongly basic anion exchanger. Issue 7 (3rd May 2018) - Wójcik, Grzegorz; Hubicki, Zbigniew
ABSTRACT: Removal of chromium(VI) ions and their reduction were studied on the anion exchanger Dowex PSR-2 in the pH range from 1.5 to 10. The parameters of Cr(VI) sorption process on the anion exchanger were calculated based on the most popular isotherm models such as: Freundlich, Langmuir, Temkin, and Dubinin–Radushkevich (D-R). The Langmuir isotherm was the most appropriate to describe Cr(VI) sorption. The Cr(VI) uptake by Dowex PSR-2 was found to follow the pseudo-second-order rate kinetics. Reduction of chromium(VI) in the pH range 1.5–10 was observed using the HPLC-ICP-MS (high-performance liquid chromatography–inductively coupled plasma-mass spectrometry) method. Oxidation of tri- n -butyl quaternary ammonium groups during the chromate (VI) removal process was observed.